A Case of Ocular Syphilis in a 36-Year-Old HIV-Positive Male. (11th August 2014) - Nguyen, Amy; Berngard, Samuel Clark; Lopez, Jay Patrick; Jenkins, Timothy C.
Abstract : The incidence of syphilis in the United States has increased markedly over the last decade, particularly among men who have sex with men (MSM). Although uncommon, ocular involvement is a potentially devastating clinical manifestation of syphilis. Human immunodeficiency virus (HIV) infection appears to increase the risk of ocular syphilis. Because of the lack of pathognomonic features for ocular syphilis and its ability to occur in both immunocompetent and immunosuppressed individuals, prompt diagnosis requires a high index of suspicion. Ocular syphilis should therefore be considered in MSM and HIV-infected patients presenting with unexplained visual complaints. Herein, we present a case of ocular syphilis in a patient with newly diagnosed HIV.